Compression of the Inferior Cava by a Plexiform Neuroma. - Croci, Fabio; Gastambide, Carmelo; Kamaid, Emil; Delgado, Bolívar; Calleriza, Fernando (Cirugía del Uruguay, 1983)
The authors present a case of compressión